Efek Strength Exercise terhadap Penurunan Gejala Akut pada Pasien dengan Rheumatoid Arthritis - Veranita, Aprillia; Rahmadi, Chandra; Siahaan, Joni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of strength exercise on reducing acute symptoms in rheumatoid arthritis. The design used is a Quasi Experiment with a two-group pretest-posttest model. The study sample consisted of 74 respondents divided into two groups: 37 respondents in the strength exercise group and 37 respondents in the education group. The sampling technique used random sampling. Data analysis was performed using the Wilcoxon test. The results showed that there were differences in the degree of knee flexion range of motion before and after doing Strength exercise in weeks 1, 2, 3, and 4. The increase occurred in week 1 (p value = 0.046), week 3 (p value = 0.005) and 4 (p value = 0.001). differences in pulse frequency before and after doing Strength exercise in weeks 1, 2, 3, and 4. The increase occurred in week 1 (p value = 0.046), week 2 (p value = 0.33), week 3 (p value = 0.005) and 4 (p value = 0.001). There was a difference in the level of knowledge of respondents before and after education. Before education, there were no respondents with good knowledge, 4 (10.8%) had sufficient knowledge, and 33 (89.2%) had poor knowledge. After education, 5 (13.5%) had good knowledge, 11 (29.7%) had sufficient knowledge, and 21 (56.8%) had poor knowledge. Conclusion: Strength exercise and education have an effect on reducing acute RA symptoms. Recommendation: Strength exercise is a good independent nursing intervention to improve patient muscle strength. Keywords: Strength exercise, Rheumatoid Arthritis, Reduction of Acute Symptoms